Antiresorptive Therapy for Osteoporosis in Older Subjects - Sølling, Anne Sophie; Laursen, Natasha Amran; Harsløf, Torben; Langdahl, Bente Lomholt (Gerontology (Basel), 2025)
Osteoporosis increases the risk of fractures and mortality, particularly in the elderly population. However, prescribing antiresorptive medication to elderly patients with osteoporosis is complex. The benefit-risk ratio should be considered for all patients but can be particularly challenging in older individuals due to factors like comorbidities, polypharmacy, fall risk, and potential rare side effects of long-term treatment. We reviewed the efficacy and safety of antiresorptive treatments, including calcium and vitamin D supplementation, in elderly patients by evaluating published trials, reviews, and meta-analyses. Our findings confirm that antiresorptive treatment for osteoporosis is both effective and safe in the elderly population. One key challenge is ensuring compliance, which can be difficult for some elderly patients. In such cases, intravenously or subcutaneously administered antiresorptive treatment should be considered to improve adherence and overall treatment compliance.